PENGARUH TINGKAT PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN BENER - Bayu Bayu Setyadi; Dian Marlina Verawati (Transpublika Publisher, 2022)
Employee performance is something that has an individual nature because each employee has a different level and performance related to his obligations. The purpose of this study was to determine the effect of education level and work experience on employee performance at the Bener District Office. The method used in this research is using quantitative methods, using 40 respondents as the sample. In collecting data, the researcher used a questionnaire distributed to the respondents which later the data would be processed using Multiple Regression Analysis using IBM SPSS Statistics 24 software. The results of the analysis found that the level of education and work experience had a positive and significant effect on the performance of Bener District Office employees.